TRADITIONAL MARKET SOLID WASTE MANAGEMENT STUDY IN KEPANJEN, MALANG DISTRICT - Hardianto Hardianto; I Nyoman Sudiasa; Shendy Hilda Sari (Konversi, 2020)
Traditional markets are commercial areas that produce household-type solid waste so that the generation, composition, and the characteristics of the solid waste in Kepanjen Market will be different. This research is related to the reduction potential to improve solid waste management with the aim of determining the generation, composition, characteristics, collection and the transportation of the solid waste. The data used in this study include operational technical solid waste data, as well as secondary data such as area, number of traders, solid waste management resources, collection facilities, transportation routes, supporting maps. Solid waste generation calculation uses load-count analysis method. Calculation of solid waste composition uses the crossroad method. Calculation of physical characteristics includes specific gravity of solid waste. Calculation of transportation of solid waste uses the Hauled Container System method. Mass balance is analyzed using recovery factor values. The results of the analysis show that the solid waste generation average is 2.94 m3/day, with a specific gravity of 190.03 kg/m3. The highest composition of solid waste is food solid waste by 28.67% and vegetable and fruit solid waste by 22.67%. These components can be used as compost raw materials. The potential reduction with the mass balance method shows that the residue is 201.49 kg/day, reduction scenario can reduce solid waste by 36.06% of the total load that must be transported to the Final Processing Site. The solid waste transport result with the capacity/size of 6-10 m3 of a transport vehicle (arm roll truck) shows that the effective working hours for 8 hours can pick up the solid waste in 1 trip, and the transport fleet can serve other markets.